Integrated phosphorus management in black gram (Vigna mungo) in western uttar pradesh during summer season - Kumar, Sandeep; Tomar, Savita; Tomar, Tejveer Singh (Annals of Agricultural Research, 2016)
A field experiment was conducted during summer seasons of 2010 and 2011 on integrated phosphorus management in blackgram to study the effect of biofertiizers (no inoculation, PSB and PSB+VAM) sources (DAP,MRP and pyrites)and levels of phosphorus (0,30 and 60 kg P2O5/ha) on the growth, yield attributes and yield, uptake and balance of nutrients in soil and economics of blackgram (Vigna mungo). Inoculation of biofertilizers significantly increased growth and yield attributes (branches/plant, dry matter/ha, nodules/plant, pods/plant, grain/pod and 1000 grain weight), grain and straw yield, nutrients uptake and residual balance( N and P) in soil and economic returns (net returns/ha and benefit cost ratio) compared to no inoculation. Dual inoculation of PSB+VAM significantly increased all these attributes as compared to PSB alone, while negative balance of 13.10kg available N was noted in no inoculation. Sources of phosphorus differed significantly in their response. DAP significantly increased growth and yield attributes, yield, nutrients uptake and economic returns as compared to MRP and Pyrites but residual nutrient balance in soil was significantly higher in MRP and pyrites than DAP. Application of 60 kg P2O5/ha resulted significant increase in all these attributes over 30 kg P2O5/ha. Absolute control (no fertilization) produced significantly poor performance of these attributes than rest treatments. A negative balance of available N and P in soil was recorded after the harvest of blackgram in absolute control and negative balance of N in no inoculation.